The persistence of memory : New Mexico's churches - Brewer, Robert; McDowell, Steve; Coles, Robert (Santa Fe : Museum of New Mexico Press, 1990)
"A harmony of pictures and words, Brewer and McDowell's The Persistence of Memory touches the essence of these living adobe churches and what they must mean to the people who built them."--John L. Kessell.--Page [4] of cover
Includes bibliographical references (p. 152).
70069
Keywords: Church buildings -- History -- Rio Grande Valley; Spaniards -- History -- Rio Grande Valley; Rio Grande Valley -- Social life and customs; Rio Grande Valley -- Church history